Search for Axionlike-Particle-Induced Prompt gamma-Ray Emission from Extragalactic Core-Collapse Supernovae with the Fermi Large Area Telescope - Meyer, Manuel; Petrushevska, Tanja (Physical Review Letters, 2020)
During a core-collapse supernova (SN), axionlike particles (ALPs) could be produced through the Primakoff process and subsequently convert into gamma rays in the magnetic field of the Milky Way. We do not find evidence for such a gamma-ray burst in observations of extragalactic SNe with the Fermi Large Area Telescope (LAT). The SN explosion times are estimated from optical light curves and we find a probability of about similar to 90% that the LAT observed at least one SN at the time of the core collapse. Under the assumption that at least one SN was contained within the LAT field of view, we exclude photon-ALP couplings greater than or similar to 2.6 x 10(-12) GeV-1 for ALP masses m(a) less than or similar to 3 x 10(-10) eV, improving previous limits from SN1987A by a factor of 2.
CRIS-Team WoS Importer:2020-06-26